Pedagogical Features Of Developing Independent Work Competencies In Future Primary School Teachers (Pedagogical Cluster-Journal of Pedagogical Developments, 2024)
In the field of primary education, the competences of teachers for independent work, in teaching students in a certain subject or topic, organizing their productive activities, using new and creative approaches, and developing themselves together with students, is an important topic aimed at achieving quality management of the educational process. This article includes teachers' abilities to manage themselves for specific goals or tasks, to solve problems and to find, apply and develop new approaches, to consolidate and share information, to analyze and collaborate with the community, to share experiences and to account for results. takes